PENGGAMBARAN METAFORIS PENGALAMAN EMOSIONAL DAN REALITAS BATIN TOKOH NOVEL KONTEMPORER RUMAH UNTUK ALIE - Nurhusna; Husna Arianti; Ramly (STKIP Subang, 2026)
Metaphorical Depiction of Emotional Experience and Inner Reality of Characters in the Novel Rumah untuk Alie by Lenn Liu. This study aims to describe the metaphorical depiction of emotional experiences and inner realities of characters in the novel Rumah untuk Alie by Lenn Liu. This research uses a qualitative descriptive approach with a literature study method. The research data consists of words, phrases, clauses, and sentences containing metaphors in the novel Rumah untuk Alie by Lenn Liu. The data source for this research is the text of the novel Rumah untuk Alie, 11th edition, 2025. Data collection is carried out through reading and recording techniques with data identification and classification stages. The research instrument is the researcher himself (human instrument) assisted by a metaphor data recording sheet. The data analysis technique uses the Miles and Huberman model which includes data reduction, data presentation, and drawing conclusions. The results of the study show that the metaphors in the novel Rumah untuk Alie are predominantly sourced from human physical and sensory experiences, such as drowning, physical injuries, building collapses, sharp object punctures, and sensations of tightness. These metaphors are used to represent the emotional experiences and inner realities of the characters, such as longing, grief, trauma, inner wounds, and emotional release. The use of metaphors serves to strengthen meaning, build character depth, and enrich the beauty of language in the novel.